WHY SHOULD THEY BE MIGRANT LABOUR? - Masyhuri, Mohammad Ali; Wibowo, Bambang Sri; Suprihandari, Miya Dewi (Media Mahardhika, 2020)
There are sources which are needed by a nation, we can say human resource and natural resource. Human resources are one of the important sources for a nation for its growth, instead of natural source. But, still, there are people who have gone to different countries to get a better life for their future as they have said or there are still unemployees number stated. This is only the writer's side of view about the human resources which have a high contribution to the growth of a nation. A nation as a great organization needs to handle its human resources to make it great in many ways of life of the global era nowadays. Human resource management will be needed here and will make many policies to handle this source instead of natural sources.  If a nation doesn?t make any policies to handle to empower, to strengthen them to be great manpower who will conquer every competition of this global era. A fact that we have seen much nowadays is being an entrepreneur. Many young generations started to get settled by doing business that brought much youth too to be hired as part-timers or full-timers, that is really great scene of our youth nowadays (www.businessdictionary.com). They tried to be on their own, they opened their mind not always to be an employee who always got monthly income, so they don?t have to think too much about their life. For those youth, being an entrepreneur is a challenge, they will make other people see that they are able to stand on their own feet. Being an entrepreneur would give them a lesson about human resource management too by doing, and it would teach them more about running and manage their own business, instead of knowing that they could get by reading, listen, and watching from their schools, university, and courses